Associação entre gengivite, fatores socioeconômicos e comportamentais em escolares na cidade de Pelotas RS - Chiapinotto, Fabiana Amaral (2011)
Periodontal disease in its destructive form is characterized as a public health problem due to its high incidence and prevalence worldwide, and may cause a negative impact on the quality of life of individuals, depending on its severity. However, few population-based studies were conducted to measure the nondestructive form of periodontal disease, gingivitis, and the factors associated with it. The aim of this study is to estimate the prevalence and severity of gingivitis in schoolchildren and test its association with demographic, socioeconomic and behavioral factors. The study had a cross-sectional school based in the city of Pelotas, Brazil. The sample consisted of children between the ages of 8 and 12 years of both sexes, attending public and private schools, randomly selected through a process of conglomerate in two stages. Data were obtained through semi-structured questionnaire directed to parents or guardians and interview and clinical oral examination performed on schoolchildren. The diagnosis of gingivitis was achieved by the Gingival Bleeding Index (GBI). The dependent variable was the presence of gingival bleeding and gingivitis and the independent variables consisted of demographic, family socioeconomic status and the behavior of children towards oral health, use of dental services, and clinical variables. For statistical analysis the data were organized into a database using Epi-Data 6.0 and the description of absolute and relative frequencies being held later. Soon after, the associations between exposures and outcomes were tested using bivariate analysis, estimating prevalence ratios and confidence intervals at 95%. Multivariate analysis was performed using Poisson regression with robust variance and a significance level of 5%. The prevalence of bleeding on probing was 78.4% (95% CI: 76.1 to 81.0), the mean and median number of sites with gingival bleeding was 3.10 and 2 (SD ± 3.22), respectively. In multivariable adjusted analysis, the presence of a greater number of sites with plaque was significantly associated with gingivitis [PR 1.89 (95% CI: 1.50 to 2.37)]. Children whose mothers had less education, were 55% more likely to have gingivitis than mothers with more years of schooling ≥ 8. Mulatto children had a 39% lower chance of having gingivitis [PR 0.61 (95% CI: 0.43 to 0.85)] compared to children of white skin. This association was observed after adjusting for other variables such as gender, skin color and age. The reported high prevalence of gingivitis among schoolchildren and the socioeconomic and behavioral factors associated whit it confirm the need for dental care as a priority in preventive measures at earlier ages, when this condition is reversible and healthy oral hygiene habits are better understood and strengthened, taking into account the role of the mother in this process